The Problem of Musical Creativity and its Relevance for Ethical and Legal Decisions towards Musical AI - Zanzarella, Ivano (Filosofia Morale/Moral Philosophy, 2024)
Today, AI and technology are no longer simple tools in music production, but active collaborators of human musicians. This raises complex questions about the nature of artificial musical creativity and its ethical and legal implications. This paper addresses such questions by considering a study case, the problem of artificial music authorship. It is argued that attributions of a moral and legal status to Musical AI technologies are closely tied to the theoretical understanding of musical creativity implicitly or explicitly presupposed, and that such attributions are necessary and desirable in present-day society because of pragmatic reasons.